The role of magnetic levitation technologies in conventional transportation systems: A review of current trends and future - Okon David, Victor; Ekanem, Imoh Ime; Uviefovwe Ohwoekevwo, Jephtar (Mechanical Technology and Engineering Insights, 2025)
Conventional transportation systems are facing increasing challenges in terms of efficiency, sustainability, and capacity. As populations continue to grow and urban areas become more congested, there is a rising need for innovative transportation solutions that can help alleviate traffic congestion, reduce emissions, and improve overall transportation efficiency. Magnetic levitation technologies have the potential to address some of these challenges by providing a fast, efficient, and environmentally friendly transportation option. This study reviewed relevant literature on the field of magnetic levitation technologies in transportation systems. Also, the current trends in the use of magnetic levitation technologies in transportation, as well as potential future applications was evaluated. The research further delve into identifying the essential benefits and setbacks of deploying maglev and its adaptation with conventional transportation systems. The research synthesizes the necessary information to provide a comprehensive overview of the role of magnetic levitation technologies in conventional transportation systems. The findings reveal that magnetic levitation technologies in transportation systems have the potential to significantly improve transportation efficiency, reduce emissions, and alleviate traffic congestion. Magnetic levitation technologies, such as maglev trains, offer faster speeds, smoother rides, and lower maintenance costs compared to traditional transportation systems. Additionally, maglev trains are environmentally friendly, as they do not rely on fossil fuels and produce zero emissions. Although integrating this technology into existing transportation infrastructure may require significant investment, planning and coordination, its implementation will help address the challenges facing modern transportation systems.